From urban sustainability transformations to green gentrification: urban renewal in Gaziosmanpaşa, Istanbul - Yazar, M; Hestad, D; Mangalagiu, D; Saysel, AK; Ma, Y; Thornton, TF (Springer Nature, 2019)
Processes aiming to achieve urban transformation that includes sustainability can result in green gentrification and thus promote exclusivist, private green spaces. At the same time, they compromise the ability of cities to promote more systemic sustainable development. Istanbul has long been a site of planned gentrification and displacement through urban renewal and regeneration projects, which have recently touted a sustainability angle. While sustainable urban renewal can have positive impacts on human health and well-being and is critical for addressing climate change and other environmental challenges, the benefits are rarely evenly distributed. Through an examination of sustainability-oriented urban renewal projects in Istanbul’s Gaziosmanpaşa district, this study shows that vulnerable residents have been displaced by the planned gentrification and that such consequences are likely to be amplified by visions of green sustainability. It also illustrates that plans to harness the city’s drive for economic growth and urban development risk making large parts of the “green” districts affordable only for relatively well-off citizens. Based on semi-structured interviews, non-participatory observation, and analysis of project and municipality-level documents, we find that even though seismic vulnerability and energy efficiency are cited as reasons for these transformations towards sustainability, policymakers are not paying sufficient attention to the political ecology of social exclusion and an increase in inequality that can result from sustainability-oriented urban renewal.